The Role of Threat, Meaning, and Religion in Political Grief - Harris, Darcy L. 19XX- (Religions, 2025)
Grief is often seen as a personal response to losing a loved one, but it can also arise from the loss of deeply held values and identities linked to social, structural, and religious spheres. Political grief is a unique form of this, stemming from political policies, laws, and social messaging that certain groups perceive as losses. As societies face political decisions and systemic failures, grief can emerge from losing trust in institutions, shared beliefs, and a sense of belonging. An outgrowth of political grief is a strain on relationships due to polarization, heightened by threat-activating events and resulting tensions. Many people turn to religion to counter feelings of vulnerability and incoherence in today’s political climate. While this may relieve anxiety and provide stability, it can also exacerbate some sources of grief. Understanding these dimensions is crucial for addressing political grief’s broader implications, as individuals and communities seek meaning and attempt to rewrite their narratives in adversity. This discussion includes defining grief beyond death-loss and exploring the interplay between social/political structures and culture. It also considers specific threats and responses, including religious alignment, focusing on recent events in the United States.